Development of a Dietary Index to Assess Overall Diet Quality for Chinese Adults: The Chinese Adults Dietary Index (P18-089-19). (13th June 2019) - Qiao, Tian; Duan, Nan; Cheng, Guo
Abstract: Objectives: To develop a Chinese Adults Dietary Index (CADI) based on current Chinese dietary guideline (2016), Chinese dietary reference intakes (2013) and existing scientific evidence and to apply it to assess the overall dietary among Chinese adults. Methods: Dietary data were obtained using 24-hour dietary recalls among 932 adults aged 18 to 70 years between 2013 and 2014. Potential confounders were also collected. The Chinese Adults Dietary Index included 17 components, which incorporated foods/food groups (grains, red meat, white meat, nuts, vegetables, fruits, dairy and dairy products, soybeans, drinking water, alcohol, SSBs, dietary variety) nutrients (dietary fiber, fatty acids, calcium, magnesium) and energy balance. The Chinese Adults Dietary Index was designed as a continuous scoring system and the range of possible CADI score was 0 to 170, with a higher score indicating better diet quality. The Pearson or Spearman correlation were used to assess the correlations between the total CADI score and age, body mass index (BMI) and nutrient adequacy ratios to test the association between CADI scores and significant indicators of diet quality. A stepwise multiple regression analysis of the data was performed to explored that if socioeconomic factors were correlated with the CADI scores. Results: The means, 25th and 75th percentiles of CADI score was 91.0, 78.5 and 102.6 points, respectively. Scores for red meat, white meat, nuts, dairy and dairy products and soybeans were much lower (<3 points), reflecting excessive consumption of red meat and insufficient consumption of white meat, nuts, dairy and dairy products and soybeans. The CADI score of women was higher than that of men ( P < 0.0001). Significant and positive correlations of CADI with the majority of nutrient adequacy ratios (energy, protein, vitamin A, vitamin C, vitamin E, thiamin, riboflavin, niacin, potassium, iron, zinc, phosphorous, copper, selenium) were observed (Pearson or Spearman correlation coefficients ranging from 0.11 to 0.56). which indicated increasing CADI scores reflected higher overall diet quality. Age, educational level and smoking status were correlated with Chinese Adults Dietary Index. Conclusions: The findings indicate that the Chinese Adults Dietary Index is capable of recognizing differences in Chinese diet, therefore, it can be used to assess overall diet quality among Chinese adults. Diet quality needs to be improved among Chinese adults. Funding Sources: This study was supported by a research grant from the National Natural Science Foundation of China (81, 673, 158). Supporting Tables, Images and/or Graphs: